2020
DOI: 10.1016/j.cub.2020.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Rho of Plants GTPases and Cytoskeletal Elements Control Nuclear Positioning and Asymmetric Cell Division during Physcomitrella patens Branching

Abstract: Highlights d MTs are essential for nuclear migration but are less involved in bulge formation d Bulge formation alters microtubule patterning and guides nuclear migration d ROP GTPases and actin play an essential role in bulge initiation d ROP4 is localized to the apical membrane and the assembling cell plate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 50 publications
0
45
0
Order By: Relevance
“…In human cell cultures, the actin cytoskeleton collaborates with the dynein-based machinery that exerts cortical pulling forces on astral MTs, thereby positioning the nucleus at the center of the cell (Kiyomitsu, 2019). In the moss Physcomitrella patens , nuclear positioning is regulated by collaborative actions between MTs and F-actin (Yi and Goshima, 2020). Whether F-actin cables directly drive movement of nucleus/chromosomes in other systems is of great interest to explore.…”
Section: Resultsmentioning
confidence: 99%
“…In human cell cultures, the actin cytoskeleton collaborates with the dynein-based machinery that exerts cortical pulling forces on astral MTs, thereby positioning the nucleus at the center of the cell (Kiyomitsu, 2019). In the moss Physcomitrella patens , nuclear positioning is regulated by collaborative actions between MTs and F-actin (Yi and Goshima, 2020). Whether F-actin cables directly drive movement of nucleus/chromosomes in other systems is of great interest to explore.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms underpinning the emergence of those tip growing cells in P. patens is remarkably well conserved throughout plants, as well as in fungi (Boyce et al, 2005): the emergence of root hairs from the root epidermis, the development of pollen tubes, and the formation of side branches in P. patens all require coordinated control of cell polarization, local cell wall loosening and cell expansion. These processes have been shown to be regulated by ROP GTPases, which localize to future bulge sites and mediate actin‐induced bulge formation (Chen et al, 2003; Jones et al, 2002; Molendijk et al, 2001; P. Yi & Goshima, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In other plant tissues, pre-ACD nuclear migrations enable the production of daughters of differing sizes and fates and also direct the relative placement of these cells [23,24]. Surprisingly, our time-lapse analyses of basl and MYR-BRX cotyledons revealed that unequally sized daughter cells could still be generated without appropriately oriented nuclear migrations ( Figures 2G and 2H).…”
Section: Nuclear Migrations Are Required For Proper Daughter Cell Plamentioning
confidence: 86%
“…Nuclear migrations preceding ACD are prevalent during plant development, and our work adds the Arabidopsis stomatal lineage to the compendium of cell types that utilize this mechanism. While several examples of polarity domains that guide pre-ACD nuclear migration have been described in other plant species [1,23,32], cortical BASL/BRXf's necessity and sufficiency for nuclear migrations and its role in coordinating the spatial positioning of successive ACDs are new. The use of time-lapse imaging to capture ACDs was critical, Please cite this article in press as: Muroyama et al, Opposing, Polarity-Driven Nuclear Migrations Underpin Asymmetric Divisions to Pattern Arabidopsis Stomata, Current Biology (2020), https://doi.org/10.1016/j.cub.2020.08.100…”
Section: Discussionmentioning
confidence: 99%